2021
DOI: 10.1136/bmjgh-2021-007479
|View full text |Cite
|
Sign up to set email alerts
|

Using geospatial models to map zero-dose children: factors associated with zero-dose vaccination status before and after a mass measles and rubella vaccination campaign in Southern province, Zambia

Abstract: IntroductionDespite gains in global coverage of childhood vaccines, many children remain undervaccinated. Although mass vaccination campaigns are commonly conducted to reach these children their effectiveness is unclear. We evaluated the effectiveness of a mass vaccination campaign in reaching zero-dose children.MethodsWe conducted a prospective study in 10 health centre catchment areas in Southern province, Zambia in November 2020. About 2 months before a national mass measles and rubella vaccination campaign… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
9
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(14 citation statements)
references
References 27 publications
2
9
0
Order By: Relevance
“…To the best of our knowledge, this is the first study to estimate the prevalence of children with zero-dose vaccination status, using nationally representative surveys of 33 countries in SSA. Our study mirrors the result of Bosch-Capblanch et al, who reported prevalence of 9.9% of zero-dose children aged 12–59 months in LMICs [ 25 ]. Therefore, the current study underscores the need to increase efforts to move the zero-dose status children to fully vaccinated status in SSA.…”
Section: Discussionsupporting
confidence: 91%
See 3 more Smart Citations
“…To the best of our knowledge, this is the first study to estimate the prevalence of children with zero-dose vaccination status, using nationally representative surveys of 33 countries in SSA. Our study mirrors the result of Bosch-Capblanch et al, who reported prevalence of 9.9% of zero-dose children aged 12–59 months in LMICs [ 25 ]. Therefore, the current study underscores the need to increase efforts to move the zero-dose status children to fully vaccinated status in SSA.…”
Section: Discussionsupporting
confidence: 91%
“…The majority of these unvaccinated children live in the inner communities of SSA countries that are difficult to access by healthcare workers [ 53 ]. In 2020, as a result of the COVID-19 pandemic, most LMICs faced several challenges in basic healthcare services without exceptions to childhood immunization [ 25 ]. Therefore, the number of zero-dose children is expected to double as a result of the COVID-19 pandemic [ 54 ].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Thus, the current level of empowerment may have been different relative to when vaccination was due. Although we have chosen a zero-dose definition used by the UNICEF and the WHO (those who received no doses of DTP [ 21 , 23 ]) and other studies [ 37 , 38 ], it is not a complete zero-dose. The idea behind the operationalization of zero-dose taking into account only DPT is because having no doses of DPT is a good proxy of poor access to routine immunization and other health services.…”
Section: Discussionmentioning
confidence: 99%